Impact of fintech regulation and data security on stability of global digital financial systems - Rudy Syafariansyah Dachlan (Lentera Negeri, 2026)
This research examines the impact of fintech regulation and data security on the stability of global digital financial systems amid rapid technological transformation and increasing cybersecurity risks. The study aims to analyze how regulatory effectiveness and cybersecurity governance contribute to maintaining financial resilience within interconnected digital economies. This research employs a library research method using primary and secondary data derived from books, scientific journals, policy reports, and relevant academic literature concerning fintech regulation, data security, and digital financial stability. Data were collected through literature review and analyzed using content analysis techniques to identify patterns, relationships, and significant findings related to digital financial governance. The findings indicate that adaptive fintech regulations, strong cybersecurity systems, and international cooperation significantly strengthen financial stability, institutional accountability, and public trust in digital financial ecosystems. The study concludes that integrated governance between regulation and data protection is essential for ensuring the sustainability and resilience of global digital financial systems.